An organization of the theoretical perspectives in the field of civic and political participation: contributions to citizenship education - Norberto Ribeiro (2017)
This article provides a review of the theoretical perspectives on civic and political participation. Four distinct views were identified in the literature: (a) The orthodox view: "Civic and political participation are always positive"; (b) The broad view: "Civic and political participation are multidimensional"; (c) The qualitative view: "Civic and political participation are not always good"; and (d) The nonconformist view: "The need to redeem the political dimension of participation." This article intends to sophisticate simplistic assumptions about civic and political participation and to provide an original organization of the theoretical perspectives in this field. Based on this analysis, this article presents suggestions for an alternative approach to citizenship education.